A transformerless Z‐source photovoltaic grid‐connected inverter with coupled inductor coil - Yunzhong Dai; Huaiyu Zhang (Micro & Nano Letters, 2024)
Abstract The quasi‐Z‐source H‐bridge grid‐connected inverter (QHGCI) is well known for its advantages of the void of the shoot‐through problem and the high DC‐voltage utilization. But the existence of the common‐mode leakage current in the power frequency cycle, lower power density, and higher thermal stress make it hard applicable to the grid‐penetrating application. Thus with the purpose to conquer the problem relating to the QHGCI, an innovative transformerless Z‐source photovoltaic grid‐connected inverter with a coupled inductor coil (TZPGCI‐CIC) is proposed. The circuitry topology and an unipolar sine pulse width modulation strategy are first introduced in short. Thereafter, the common‐mode voltage in the whole working process is derived and evaluated through the detailed operating mode analysis, in which a constant value of it has been theoretically revealed. Lastly, a prototype platform of TZPGCI‐CIC is set up and its good performance on leakage current suppression, and lower thermal stress are validated with the experimental results.